The impact of axillary lymph node dissection on the prognosis of breast cancer patients undergoing up-front mastectomy with Sentinel lymph node micrometastases - Wu Ding; YongTian Chen; Yingli Lin; Xiaoliang Chen (Scientific Reports)
Abstract Traditionally, completion axillary lymph node dissection (ALND) has been standard for breast cancer patients with positive sentinel lymph nodes (SLNs). However, ALND poses risks of morbidity. Recent trials suggest omission of ALND may be safe in selected cases. Controversy exists regarding ALND omission in mastectomy patients with micrometastases. We retrospectively analyzed data from 12 centers in China and the Surveillance, Epidemiology, and End Results (SEER) database. Patients with T1-2 breast cancer and SLN micrometastases who underwent up-front mastectomy were included. Patients were categorized into two groups: Non-ALND and ALND. Clinicopathological factors and survival outcomes were compared between the two groups. A total of 118 patients from 12 centers in China and 4,884 patients from the SEER database were included in the analysis. The Non-ALND group demonstrated non-inferiority in terms of recurrence-free survival (RFS), locoregional recurrence-free survival (LRFS), breast cancer-specific survival (BCSS), and overall survival (OS) when compared to the ALND group. Multivariable analysis identified significant predictors of survival outcomes. This study supports the omission of ALND in T1-2N1mi breast cancer patients undergoing mastectomy, demonstrating comparable survival outcomes to those undergoing ALND. Proper patient selection is essential for tailored treatment strategies.